Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
x = -10
Step-by-step explanation:
2(x+3) = x-4 --> multiply (x+2) times 2
2x+6 = x - 4 --> subtract x from both sides
x+6 = -4 --> subtract 6 from both sides
x = -10
Answer:
x = -10
Step-by-step explanation:
Simplify both sides of the equation.
2 (x+3) = x − 4
(2) (x) + (2) (3) = x + −4 (Distribute)
2x + 6 = x + − 4
2x + 6 = x − 4
Subtract x (1x) from both sides
2x + 6 − x = x − 4 − x
x + 6 = − 4
Subtract 6 from both sides
x + 6 − 6 = − 4 − 6
x = -10
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.